Optical glass, glass preform, optical element and apparatus

CN122958054APending Publication Date: 2026-10-23CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611343678.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

为实现光学系统的轻量化,将光学玻璃加工成较小或较薄的光学元件时,若光学玻璃的杨氏模量较小,则光学元件在使用过程中易产生形变,从而导致成像质量下降

Benefits of technology

[0028]本发明的有益效果是:通过合理的组分设计,本发明光学玻璃在具有高折射率低色散的同时还具有较高的杨氏模量,满足高性能设备的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides an optical glass with high Young's modulus, and a glass preform, an optical element and an apparatus made of the optical glass. The optical glass contains, in terms of percentage by weight, B2O3: 8-18%; SiO2: 3-13%; La2O3: 31-43%; ZnO: 1-9%; Gd2O3: 7-21%; Y2O3: 3-14%; ZrO2: 2-12%; Nb2O5: 2-12%; Al2O3: more than 0 but less than or equal to 5%, wherein Al2O3 / (Y2O3+ZnO-SiO2) is 0.01-5.00. Through reasonable component design, the optical glass has high refractive index, low dispersion and high Young's modulus, and meets the application of high-performance apparatuses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass technology, and in particular to an optical glass with a high Young's modulus, as well as glass preforms, optical elements and devices made therefrom. Background Technology

[0002] In recent years, equipment using optical systems has developed rapidly in terms of digitization and high definition. In various fields such as digital cameras and camcorders, and projectors and projection televisions, there is an increasing demand for reducing the number of optical components such as lenses and prisms used in optical systems, and for making the overall optical system lighter and smaller. Lenses formed from high-refractive-index, low-dispersion optical glass, combined with lenses formed from low-refractive-index, high-dispersion optical glass, can be combined to form composite lenses, which can correct chromatic aberration and achieve compactness of optical systems. Therefore, high-refractive-index, low-dispersion optical glass occupies a very important position as an optical component in imaging optical systems, projectors, and other projection optical systems. To achieve lightweight optical systems, when processing optical glass into smaller or thinner optical components, if the Young's modulus of the optical glass is small, the optical component is prone to deformation during use, leading to a decrease in image quality. Therefore, it is desirable for optical glass to have both high refractive index and low dispersion, as well as a high Young's modulus. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide an optical glass with a high Young's modulus, as well as glass preforms, optical elements and devices made therefrom.

[0004] The technical solution adopted by this invention to solve the technical problem is:

[0005] (1) Optical glass, the composition of which is expressed as a percentage by weight, contains: B2O3: 8%~18%; SiO2: 3%~13%; La2O3: 31%~43%; ZnO: 1%~9%; Gd2O3: 7%~21%; Y2O3: 3%~14%; ZrO2: 2%~12%; Nb2O5: 2%~12%; Al2O3: greater than 0 but less than or equal to 5%, of which Al2O3 / (Y2O3+ZnO-SiO2) is 0.01~5.00.

[0006] (2) The optical glass according to (1) further comprises, by weight percentage: TiO2: 0-3%; and / or WO3: 0-3%; and / or Ta2O5: 0-3%; and / or Yb2O3: 0-5%; and / or Rn2O: 0-4%; and / or RO: 0-4%; and / or GeO2: 0-3%; and / or P2O5: 0-3%; and / or clarifying agent: 0-1%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0007] (3) Optical glass containing the necessary components B2O3, SiO2, La2O3, ZnO, Gd2O3, Y2O3, ZrO2, Nb2O5, and Al2O3, the components of which are expressed as weight percentages, with Al2O3 / (Y2O3+ZnO-SiO2) being 0.01 to 5.00, and the refractive index n of the optical glass. d The Abbe number ν ranges from 1.825 to 1.875. d The value ranges from 40.50 to 46.00, and the Young's modulus is above 105.0 GPa.

[0008] (4) The optical glass according to (3) comprises, by weight percentage: B2O3: 8%–18%; and / or SiO2: 3%–13%; and / or La2O3: 31%–43%; and / or ZnO: 1%–9%; and / or Gd2O3: 7%–21%; and / or Y2O3: 3%–14%; and / or ZrO2: 2%–12%; and / or Nb2O5: 2%–12%; and / or Al2O3: greater than 0 but less than or equal to 5%; and / or TiO2: 0%–3%; And / or WO3: 0-3%; and / or Ta2O5: 0-3%; and / or Yb2O3: 0-5%; and / or Rn2O: 0-4%; and / or RO: 0-4%; and / or GeO2: 0-3%; and / or P2O5: 0-3%; and / or clarifying agent: 0-1%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0009] (5) The optical glass according to any one of (1) to (4) has components expressed as weight percentages that satisfy one or more of the following conditions:

[0010] 1) The ratio of Al2O3 / (Y2O3+ZnO-SiO2) is 0.05 to 3.00, preferably 0.10 to 1.00;

[0011] 2) The ratio of (Gd2O3+Y2O3-B2O3) / Nb2O5 is 0.05 to 5.00, preferably 0.30 to 4.00, and more preferably 0.80 to 1.80;

[0012] 3) The ratio of Gd2O3 / (ZnO+Y2O3) is 0.50 to 3.00, preferably 0.80 to 2.00, and more preferably 1.00 to 1.70;

[0013] 4) The ratio of B2O3 to Y2O3 is 1.00 to 5.00, preferably 1.20 to 4.00, and more preferably 1.50 to 2.50;

[0014] 5) The ZrO2 / ZnO ratio is 0.30 to 3.00, preferably 0.80 to 2.50, and more preferably 1.00 to 2.00;

[0015] 6) The ratio of Al2O3 / (SiO2+ZnO+Y2O3-Gd2O3-Ta2O5) is 0.02 to 6.50, preferably 0.07 to 4.00, and more preferably 0.15 to 1.00;

[0016] 7) The SiO2 / (ZnO-Ta2O5-TiO2-WO3-RO-Rn2O) ratio is 0.50 to 6.00, preferably 1.00 to 4.00, and more preferably 1.20 to 2.50;

[0017] 8) The ratio of Al2O3 / (ZnO-Ta2O5-WO3) is 0.01 to 3.00, preferably 0.05 to 2.00, and more preferably 0.10 to 0.70;

[0018] 9) The ratio of (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) is 0.02 to 3.50, preferably 0.05 to 2.00, and more preferably 0.10 to 0.80;

[0019] 10) The ratio of (Y2O3-ZnO-Ta2O5-WO3) / ZnO is 0.10 to 3.50, preferably 0.20 to 2.00, and more preferably 0.30 to 1.50;

[0020] 11) The ratio of (ZnO+Rn2O) / Y2O3 is 0.10 to 1.00, preferably 0.20 to 0.90, and more preferably 0.40 to 0.80;

[0021] 12) The ratio of (TiO2+Ta2O5+WO3) / Nb2O5 is 0.60 or less, preferably 0.30 or less, and more preferably 0.20 or less;

[0022] 13) The ratio of (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.33 or less, preferably (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.20 or less, more preferably (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.15 or less, wherein Rn2O is one or more of Li2O, Na2O, and K2O, and RO is one or more of MgO, CaO, SrO, and BaO.

[0023] (6) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentages, wherein: B2O3: 10% to 17%, preferably B2O3: 12% to 16%; and / or SiO2: 4% to 11%, preferably SiO2: 5.5% to 9%; and / or ZnO: 1.5% to 8%, preferably ZnO: 2% to 6%; and / or La2O3: 33% to 42%, preferably La2O3: 36% to 41%; and / or Gd2O3: 8% to 20%, preferably Gd2O3: 8% to 20%. d2O3: 10.5%–18%; and / or Y2O3: 5%–12%, preferably Y2O3: 6%–10%; and / or Yb2O3: 0%–3%, preferably Yb2O3: 0%–1%, more preferably without Yb2O3; and / or ZrO2: 3%–10%, preferably ZrO2: 4%–8%; and / or Nb2O5: 3%–10%, preferably Nb2O5: 4%–8%; and / or Al2O3: 0.1%–4%, preferably Al2O3: 0.5%–2.5%. %; and / or TiO2: 0-2%, preferably TiO2: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-0.5%, more preferably WO3-free; and / or Ta2O5: 0-2%, preferably Ta2O5: 0-0.5%, more preferably Ta2O5-free; and / or Rn2O: 0-2%, preferably Rn2O: 0-1%, more preferably Rn2O-free; and / or RO: 0-2%, preferably RO: 0-1%, more preferably RO-free; and / or Ge O2: 0-2%, preferably GeO2: 0-1%, more preferably without GeO2; and / or P2O5: 0-2%, preferably P2O5: 0-1%, more preferably without P2O5; and / or clarifying agent: 0-0.5%, preferably clarifying agent: 0-0.2%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0024] (7) The optical glass according to any one of (1) to (4), wherein the refractive index n of the optical glass is d The Abbe number is 1.825–1.875, preferably 1.830–1.870, more preferably 1.840–1.858; and / or the Abbe number ν. d The coefficient of thermal expansion is 40.50 to 46.00, preferably 41.00 to 45.00, more preferably 41.50 to 44.00; and / or the Young's modulus is 105.0 GPa or more, preferably 110.0 GPa or more, more preferably 118.0 GPa or more; and / or the coefficient of thermal expansion α is 40.50 to 46.00, preferably 41.00 to 45.00, more preferably 41.50 to 44.00; and / or the coefficient of thermal expansion α is 105.0 GPa or more, preferably 110.0 GPa or more; and / or the coefficient of thermal expansion α is 118.0 GPa or more. 100℃ / 300℃ 100×10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 90×10 -7 / K or below; and / or water resistance stability of Class 2 or above, preferably Class 1; and / or weather resistance of Class 2 or above, preferably Class 1; and / or density of 5.30 g / cm³. 3 The preferred value is 5.20 g / cm³. 3 The following is a preferred value: 5.10 g / cm³ 3 The following is a further preferred value: 5.05 g / cm³ 3 The following; and / or Knoop hardness is 610×10 7 Pa or higher, preferably 630 × 10 Pa 7 Pa or higher, more preferably 650 × 10 Pa 7 Pa or above; and / or a transition temperature of 685°C to 720°C, preferably 690°C to 715°C, more preferably 690°C to 710°C; and / or a colorimetric intensity λ 70 The wavelength is 385nm or less, preferably 380nm or less, more preferably 375nm or less; and / or the colorimetric intensity λ5 is 340nm or less, preferably 335nm or less, more preferably 325nm or less; and / or the abrasion degree is 75-110, preferably 80-105, more preferably 85-100; and / or the bubble degree is A grade or higher, preferably A0 grade or higher, more preferably A 00 Level; and / or relative partial dispersion deviation value ΔP g,F It is less than -0.0030, preferably less than -0.0050, and more preferably less than -0.0070.

[0025] (8) Glass preforms, made of any of the optical glass described in (1) to (7).

[0026] (9) Optical element, made of any of the optical glass described in (1) to (7), or made of the glass preform described in (8).

[0027] (10) An apparatus comprising any one of the optical glass described in (1) to (7) and / or comprising the optical element described in (9).

[0028] The beneficial effects of this invention are: through reasonable component design, the optical glass of this invention has a high refractive index and low dispersion, as well as a high Young's modulus, which meets the application requirements of high-performance equipment. Detailed Implementation

[0029] The embodiments of the optical glass of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of the present invention. Furthermore, regarding repeated descriptions, although there are appropriate omissions, this will not limit the spirit of the invention. In the following text, the optical glass of the present invention may be simply referred to as glass.

[0030] Optical Glass

[0031] The composition range of each component (ingredient) of the optical glass of the present invention will be described below. In the present invention, unless otherwise specified, the content of each component, the total content, and the total content are all expressed as weight percentages (wt%), that is, the weight percentage of the content of each component, the total content, and the total content relative to the total amount of glass material converted into oxide composition. Here, "converted into oxide composition" means that when the oxides, complex salts, and hydroxides used as raw materials for the optical glass of the present invention decompose and transform into oxides upon melting, the total amount of such oxides is taken as 100%.

[0032] Unless otherwise specified in the specific context, the numerical ranges listed in this invention include upper and lower limits, and "above" and "below" include endpoint values ​​and all integers and fractions included in the range, but are not limited to the specific values ​​listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.

[0033] <Essential and Optional Components>

[0034] B2O3 is a component of the glass network forging system, which can improve the stability, melt flow properties, and resistance to crystallization of glass. However, if the B2O3 content is too high, the chemical stability and mechanical properties of the glass will decrease, the devitrification resistance will decline, and it will be difficult to obtain the desired high refractive index. Therefore, the B2O3 content in this invention is 8% to 18%, preferably 10% to 17%, and more preferably 12% to 16%. In some embodiments, the B2O3 content can be 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0035] SiO2 can increase the viscosity of molten glass, improve its resistance to devitrification and weathering, and help reduce glass coloration. However, if its content is too high, the difficulty of melting the glass increases, the transition temperature rises, and the refractive index decreases. Therefore, the SiO2 content in this invention is 3% to 13%, preferably 4% to 11%, and more preferably 5.5% to 9%. In some embodiments, the SiO2 content can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0036] ZnO can improve the chemical stability and meltability of glass, lower the glass transition temperature, and enhance the weather resistance of glass. However, when its content is too high, it will increase the corrosion of platinum utensils during the melting process, reduce the service life of the furnace, and negatively affect the glass's resistance to crystallization. Therefore, the ZnO content in this invention is 1% to 9%, preferably 1.5% to 8%, and more preferably 2% to 6%. In some embodiments, the ZnO content can be greater than 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, 7.3%, 7.5%, 7.7%, 8%, 8.3%, 8.5%, 8.7%, 9%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0037] La2O3 is a high-refractive-index, low-dispersion component that can increase the refractive index of glass and regulate dispersion, improve the thermal and chemical stability of glass, and reduce the high-temperature viscosity of glass. However, if its content is too high, the anti-crystallization performance of glass decreases and the transition temperature increases. Therefore, the content of La2O3 in this invention is 31% to 43%, preferably 33% to 42%, and more preferably 36% to 41%. In some embodiments, the content of La2O3 can be 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0038] Gd₂O₃ can increase the refractive index of glass and improve its resistance to crystallization. However, if its content is too high, the glass's resistance to devitrification and chemical stability will deteriorate, and ΔP will decrease. g,F The value increases. Therefore, the content of Gd2O3 in this invention is 7% to 21%, preferably 8% to 20%, and more preferably 10.5% to 18%. In some embodiments, the content of Gd2O3 can be 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0039] Y₂O₃ can improve the refractive index and anti-crystallization properties of glass, as well as its hardness and stability. However, if its content is too high, the chemical stability and weather resistance of the glass will deteriorate. Therefore, the Y₂O₃ content in this invention is 3% to 14%, preferably 5% to 12%, and more preferably 6% to 10%. In some embodiments, the Y₂O₃ content can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0040] In some embodiments, by maintaining the ratio of B2O3 content to Y2O3 content (B2O3 / Y2O3) in the range of 1.00 to 5.00, it is possible to improve the bubble count of the glass while preventing an increase in the coefficient of thermal expansion. Therefore, a B2O3 / Y2O3 ratio of 1.00 to 5.00 is preferred, a B2O3 / Y2O3 ratio of 1.20 to 4.00 is more preferred, and a B2O3 / Y2O3 ratio of 1.50 to 2.50 is even more preferred. In some implementations, the value of B2O3 / Y2O3 can be 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0041] In some embodiments, the ratio of Gd2O3 content to the total content of ZnO and Y2O3 (ZnO+Y2O3), Gd2O3 / (ZnO+Y2O3), is controlled within the range of 0.50 to 3.00. This can reduce the coefficient of thermal expansion of the glass while improving its bubble level. Therefore, it is preferable that Gd2O3 / (ZnO+Y2O3) is 0.50 to 3.00, more preferably 0.80 to 2.00, and even more preferably 1.00 to 1.70. In some implementations, the value of Gd₂O₃ / (ZnO+Y₂O₃) can be 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, or 1. 35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0042] Yb₂O₃ is a high-refractive-index, low-dispersion component that can improve the refractive index of glass. However, if its content exceeds 5%, the glass's resistance to crystallization decreases. Therefore, the content of Yb₂O₃ is 0–5%, preferably 0–3%, and more preferably 0–1%. In some embodiments, it is further preferred that Yb₂O₃ is not present. In some embodiments, the content of Yb₂O₃ can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0043] ZrO2 can improve the refractive index and devitrification resistance of glass, as well as its chemical stability and mechanical properties. However, if its content is too high, the melting difficulty of the glass increases, making it prone to inclusions and reducing light transmittance, while also decreasing the glass's resistance to crystallization. Therefore, the ZrO2 content in this invention is 2%–12%, preferably 3%–10%, and more preferably 4%–8%. In some embodiments, the ZrO2 content can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, or 12%.

[0044] And so on, as well as all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0045] In some embodiments, controlling the ratio of ZrO2 content to ZnO content (ZrO2 / ZnO) within the range of 0.30 to 3.00 can optimize the abrasion resistance of the glass while reducing the glass transition temperature. Therefore, a ZrO2 / ZnO ratio of 0.30 to 3.00 is preferred, a ZrO2 / ZnO ratio of 0.80 to 2.50 is more preferred, and a ZrO2 / ZnO ratio of 1.00 to 2.00 is even more preferred. In some implementations, the ZrO2 / ZnO value can be 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1 27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0046] Nb₂O₅ can increase the refractive index of glass, improve its thermal stability and devitrification resistance, but if its content is too high, the light transmittance and anti-crystallization properties of the glass will decrease. Therefore, the Nb₂O₅ content is 2% to 12%, preferably 3% to 10%, and more preferably 4% to 8%. In some embodiments, the Nb₂O₅ content can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0047] In some implementations, by controlling (Gd2O3+Y2O3-B2O3) / Nb2O5 within the range of 0.05 to 5.00, the ΔP of the glass can be reduced. g,FWhile maintaining the desired value, it is also important to prevent the glass density from increasing. Therefore, it is preferable that the ratio of (Gd2O3+Y2O3-B2O3) / Nb2O5 is 0.05 to 5.00, more preferably 0.30 to 4.00, and even more preferably 0.80 to 1.80. In some implementations, the value of (Gd₂O₃+Y₂O₃-B₂O₃) / Nb₂O₅ can be 0.05, 0.07, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, or 0.6. 0, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.3 5, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.4 0, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0048] Al2O3 can reduce the thermal expansion coefficient and ΔP of glass. g,FThe Al2O3 content improves the glass's resistance to crystallization and thermal stability. However, excessively high Al2O3 content will lead to an increase in the glass transition temperature and a decrease in its meltability. Therefore, in this invention, the Al2O3 content is greater than 0 but less than or equal to 5%, preferably 0.1% to 4%, and more preferably 0.5% to 2.5%. In some embodiments, the Al2O3 content can be greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0049] In some embodiments, by controlling the Al2O3 / (Y2O3+ZnO-SiO2) ratio within the range of 0.01 to 5.00, the Young's modulus of the glass can be increased while simultaneously achieving a suitable degree of wear resistance. Therefore, it is preferable that the Al2O3 / (Y2O3+ZnO-SiO2) ratio is 0.01 to 5.00, more preferably 0.05 to 3.00, and even more preferably 0.10 to 1.00. In some implementations, the value of Al2O3 / (Y2O3+ZnO-SiO2) can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, or 0.4. 7, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1. 27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0050] TiO2 can improve the refractive index and dispersion of glass, and enhance its thermal stability. However, if its content is too high, the visible light transmittance and resistance to crystallization of the glass will decrease, and ΔP will also decrease. g,FThe value increases. Therefore, the TiO2 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, the TiO2 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0051] Ta₂O₅ can increase the refractive index and resistance to crystallization of glass, but if its content is too high, the meltability of the glass deteriorates. Compared with other components, Ta₂O₅ is expensive, and from a practical and cost perspective, its usage should be minimized. Therefore, the content of Ta₂O₅ in this invention is 0-3%, preferably 0-2%, and more preferably 0-0.5%. In some embodiments, the content of Ta₂O₅ can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0052] In some embodiments, by controlling the Al2O3 / (SiO2+ZnO+Y2O3-Gd2O3-Ta2O5) ratio within the range of 0.02 to 6.50, the Young's modulus of the glass can be improved, and the glass can have a suitable abrasion resistance. Therefore, it is preferable that the Al2O3 / (SiO2+ZnO+Y2O3-Gd2O3-Ta2O5) ratio is 0.02 to 6.50, more preferably 0.07 to 4.00, and even more preferably 0.15 to 1.00. In some embodiments, Al2O3 / (SiO2+ZnO+Y2O3-Gd2O3-Ta2O5) can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.5 5, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1. 45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0053] In some implementations, by controlling (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) within the range of 0.02 to 3.50, the ΔP of the glass can be reduced. g,F While maintaining the desired value, it is also important to prevent an increase in the density of the glass. Therefore, the preferred ratio of (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) is 0.02 to 3.50, more preferably (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) is 0.05 to 2.00, and even more preferably (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) is 0.10 to 0.80. In some implementations, the value of (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, or 0.3. 5, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1. 77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0054] WO3 can improve the refractive index and mechanical strength of glass, lower the glass transition temperature, and improve the glass's resistance to crystallization. However, if its content is too high, the glass's resistance to devitrification and light transmittance will decrease. Therefore, the WO3 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-0.5%. In some embodiments, it is further preferred that it does not contain WO3. In some embodiments, the WO3 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0055] In some embodiments, by controlling the Al2O3 / (ZnO-Ta2O5-WO3) ratio within the range of 0.01 to 3.00, the light transmittance of the glass can be improved while simultaneously enhancing its weather resistance. Therefore, it is preferable that the Al2O3 / (ZnO-Ta2O5-WO3) ratio is 0.01 to 3.00, more preferably 0.05 to 2.00, and even more preferably 0.10 to 0.70. In some implementations, the value of Al2O3 / (ZnO-Ta2O5-WO3) can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, or 0.3. 5, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1. 03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0056] In some embodiments, setting the (Y₂O₃-ZnO-Ta₂O₅-WO₃) / ZnO value in the range of 0.10 to 3.50 can improve the hardness of the glass while reducing its coefficient of thermal expansion. Therefore, it is preferable that the (Y₂O₃-ZnO-Ta₂O₅-WO₃) / ZnO value is 0.10 to 3.50, more preferably 0.20 to 2.00, and even more preferably 0.30 to 1.50. In some implementations, the value of (Y₂O₃-ZnO-Ta₂O₅-WO₃) / ZnO can be 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83 The values ​​are 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0057] In some embodiments, the ratio of the total content of TiO2, Ta2O5, and WO3 (TiO2+Ta2O5+WO3) to the content of Nb2O5 (TiO2+Ta2O5+WO3) / Nb2O5 is controlled to be below 0.60, which can reduce the density of the glass and prevent the water resistance of the glass from deteriorating. Therefore, it is preferable that (TiO2+Ta2O5+WO3) / Nb2O5 is below 0.60, more preferably (TiO2+Ta2O5+WO3) / Nb2O5 is below 0.30, and even more preferably (TiO2+Ta2O5+WO3) / Nb2O5 is below 0.20. In some implementations, the value of (TiO2+Ta2O5+WO3) / Nb2O5 can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0058] Alkali metal oxides Rn₂O (Rn₂O is one or more of Li₂O, Na₂O, and K₂O) can lower the glass transition temperature, adjust the optical constant and high-temperature viscosity of the glass, and improve the glass's meltability. However, when its content is too high, the glass's devitrification resistance and chemical stability decrease, and it is difficult to obtain the desired high refractive index. Therefore, the Rn₂O content in this invention is 0–4%, preferably 0–2%, and more preferably 0–1%. In some embodiments, it is further preferred that Rn₂O is not present. In some embodiments, it is further preferred that Li₂O, and / or Na₂O, and / or K₂O are not present. In some embodiments, the content of Rn2O can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the Li₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the Na₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.In some embodiments, the K2O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0059] In some embodiments, by controlling the ratio of the total content of ZnO and Rn2O (ZnO+Rn2O) to the content of Y2O3 (ZnO+Rn2O) / Y2O3 within the range of 0.10 to 1.00, the bubble count of the glass can be improved while preventing a decrease in the hardness of the glass. Therefore, it is preferable that (ZnO+Rn2O) / Y2O3 is 0.10 to 1.00, more preferably 0.20 to 0.90, and even more preferably 0.40 to 0.80. In some implementations, the value of (ZnO+Rn2O) / Y2O3 can be 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0060] Alkaline earth metal oxides (RO, which is one or more of MgO, CaO, SrO, and BaO) can adjust the optical constants of glass and optimize its chemical stability. However, when their content is too high, the glass's devitrification resistance decreases, and it is difficult to obtain the desired high refractive index. Therefore, the RO content is 0–4%, preferably 0–2%, and more preferably 0–1%. In some embodiments, it is further preferred that RO is not present. In some embodiments, it is further preferred that MgO, and / or CaO, and / or SrO, and / or BaO are not present. In some embodiments, the RO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the MgO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the CaO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.In some embodiments, the SrO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the BaO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0061] In some embodiments, by keeping the SiO2 / (ZnO-Ta2O5-TiO2-WO3-RO-Rn2O) ratio in the range of 0.50 to 6.00, the hardness of the glass can be increased while the coefficient of thermal expansion of the glass is reduced. Therefore, it is preferable that the SiO2 / (ZnO-Ta2O5-TiO2-WO3-RO-Rn2O) ratio is 0.50 to 6.00, more preferably 1.00 to 4.00, and even more preferably 1.20 to 2.50. In some implementations, the value of SiO2 / (ZnO-Ta2O5-TiO2-WO3-RO-Rn2O) can be 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.6 7, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3 60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0062] GeO2 improves the refractive index and devitrification resistance of glass, but if its content is too high, the chemical stability of the glass decreases. Compared with other components, GeO2 is very expensive, and from the perspective of glass raw material cost, its usage should be minimized. Therefore, the GeO2 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that GeO2 is not present. In some embodiments, the GeO2 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0063] In some embodiments, by controlling the ratio of (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO to below 0.33, the glass transition temperature can be reduced while preventing a deterioration in the Young's modulus of the glass. Therefore, it is preferable that the ratio of (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is below 0.33, more preferably below 0.20, and even more preferably below 0.15. In some implementations, the value of (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0064] P2O5 can appropriately improve the devitrification resistance of glass, but if its content is too high, the chemical stability and anti-crystallization properties of the glass will decrease. Therefore, the P2O5 content is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that no P2O5 is present. In some embodiments, the P2O5 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0065] In this invention, by using one or more components selected from Sb₂O₃, SnO₂, and CeO₂ as a clarifying agent containing 0-1%, the clarification effect of the glass can be improved and the bubble content of the glass optimized. Preferably, the content of the clarifying agent is 0-0.5%, more preferably 0-0.2%. In some embodiments, the content of the clarifying agent can be 0, greater than 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0066] <Components that should not be present>

[0067] In the glass of this invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this invention to improve visible light transmittance. Therefore, it is preferable that the glass does not contain these oxides, especially for optical glass where transmittance in the visible light region is required.

[0068] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to avoid the presence of these substances, except where their contamination is unavoidable. As a result, the optical glass becomes virtually free of pollutants. Therefore, the optical glass of this invention can be manufactured, processed, and disposed of even without special environmental countermeasures.

[0069] To achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0070] The terms "not containing" and "0" used herein mean that the compound, molecule, or element was not intentionally added to the optical glass of this invention as a raw material; however, as raw materials and / or equipment used in the production of optical glass, there may be certain unintentionally added impurities or components that may be present in small or trace amounts in the final optical glass, and such cases are also within the scope of protection of this patent.

[0071] The performance of the optical glass of the present invention will now be described.

[0072] <Refractive Index and Abbe Number>

[0073] The refractive index (n) of optical glass d ) and Abbe number (ν) d Tested according to the method specified in the national standard GB / T 7962.1—2010.

[0074] In some embodiments, the refractive index (n) of the optical glass of the present invention d The lower limit for the refractive index (n) is 1.825, preferably 1.830, and more preferably 1.840. In some embodiments, the refractive index (n) of the optical glass of the present invention is... d The upper limit for the refractive index (n) is 1.875, preferably 1.870, and more preferably 1.858. In some embodiments, the refractive index (n) of the optical glass is... d The range can be 1.825, 1.827, 1.830, 1.833, 1.835, 1.837, 1.840, 1.843, 1.845, 1.847, 1.850, 1.853, 1.855, 1.857, 1.858, 1.860, 1.863, 1.865, 1.867, 1.870, 1.873, 1.875, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0075] In some embodiments, the Abbe number (ν) of the optical glass of the present invention d The lower limit for the Abbe number (ν) is 40.50, preferably 41.00, and more preferably 41.50. In some embodiments, the Abbe number (ν) of the optical glass of the present invention is... d The upper limit for the Abbe number (ν) is 46.00, preferably 45.00, and more preferably 44.00. In some embodiments, the Abbe number (ν) of the optical glass is... d The values ​​can be 40.50, 40.70, 41.00, 41.30, 41.50, 41.70, 42.00, 42.30, 42.50, 42.70, 43.00, 43.30, 43.50, 43.70, 44.00, 44.30, 44.50, 44.70, 45.00, 45.30, 45.50, 45.70, 46.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0076] Coefficient of thermal expansion

[0077] The coefficient of thermal expansion of optical glass (α) 100℃ / 300℃ Data were tested at 100℃~300℃ according to the method specified in the national standard GB / T7962.16—2010.

[0078] In some embodiments, the coefficient of thermal expansion (α) of the optical glass of the present invention is... 100℃ / 300℃ ) is 100×10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 90×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion of the optical glass (α) is... 100℃ / 300℃ ) can be 100×10 -7 / K、99×10 -7 / K、98×10 -7 / K、97×10 -7 / K、96×10 -7 / K、95×10 -7 / K、94×10 -7 / K、93×10 -7 / K、92×10 -7 / K、91×10 -7 / K、90×10 -7 / K、89×10 -7 / K、88×10 -7 / K、87×10 -7 / K、86×10 -7 / K、85×10-7 / K、84×10 -7 / K、83×10 -7 / K、82×10 -7 / K、81×10 -7 / K、80×10 -7 / K, etc., and all ranges and subranges between the above values. It should be understood that, in the implementation, any of the above ranges can be combined with any other range.

[0079] <Stability under water resistance>

[0080] Water resistance stability of optical glass (D) W (Powder method) Tested according to the method specified in the national standard GB / T 17129. In this invention, the stability of water resistance can be simply referred to as water resistance.

[0081] In some embodiments, the water resistance stability (D) of the optical glass of the present invention is... W There are two or more categories, with category 1 being preferred.

[0082] <Weather resistance>

[0083] The weather resistance (CR) test method for optical glass is as follows: The glass sample is placed in a test chamber with a relative humidity of 90% and saturated water vapor. The temperature is alternated between 40℃ and 50℃ every hour for 15 cycles. Weather resistance is classified according to the change in turbidity before and after the sample placement. The weather resistance classification is shown in Table 1.

[0084] Table 1.

[0085]

[0086] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or above, preferably Class 1.

[0087] <Density>

[0088] The density (ρ) of optical glass is tested according to the method specified in the national standard GB / T7962.20—2010.

[0089] In some embodiments, the density (ρ) of the optical glass of the present invention is 5.30 g / cm³. 3 The preferred value is 5.20 g / cm³. 3 The following is a preferred value: 5.10 g / cm³ 3 The following is a further preferred value: 5.05 g / cm³ 3 Below. In some embodiments, the density (ρ) of the optical glass can be 5.30 g / cm³. 3 5.29 g / cm3 5.28g / cm 3 5.27 g / cm 3 5.26 g / cm 3 5.25g / cm 3 5.24 g / cm 3 5.23 g / cm 3 5.22g / cm 3 5.21 g / cm 3 5.20g / cm 3 5.19 g / cm 3 5.18 g / cm 3 5.17 g / cm 3 5.16 g / cm 3 5.15g / cm 3 5.14 g / cm 3 5.13 g / cm 3 5.12 g / cm 3 5.11 g / cm 3 5.10 g / cm 3 5.09 g / cm 3 5.08g / cm 3 5.07 g / cm 3 5.06 g / cm 3 5.05g / cm 3 5.04 g / cm 3 5.03 g / cm 3 5.02 g / cm 3 5.01 g / cm 3 5.00g / cm 3 4.99g / cm 3 4.98g / cm 3 4.97g / cm 3 4.96 g / cm 3 4.95g / cm 3 4.94 g / cm 3 4.93 g / cm 3 4.92g / cm 3 4.91 g / cm 3 And so on, as well as all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0090] Knoop Hardness

[0091] Knoop hardness (H) of optical glass KThe test was conducted according to the test method specified in the national standard GB / T7962.18-2010. In this invention, Knoop hardness can be simply referred to as hardness.

[0092] In some embodiments, the Knoop hardness (H) of the optical glass of the present invention is... K ) is 610×10 7 Pa or higher, preferably 630 × 10 Pa 7 Pa or higher, more preferably 650 × 10 Pa 7 Pa or higher. In some embodiments, the Knoop hardness (H) of the optical glass is... K (It can be 610×10) 7 Pa, 615×10 7 Pa, 620×10 7 Pa, 625×10 7 Pa, 630×10 7 Pa, 635×10 7 Pa, 640×10 7 Pa, 645×10 7 Pa, 650×10 7 Pa, 655×10 7 Pa, 660×10 7 Pa, 665×10 7 Pa, 670×10 7 Pa, 675×10 7 Pa, 680×10 7 Pa, 685×10 7 Pa, 690×10 7 Pa, etc., and all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the aforementioned ranges can be combined with any other range.

[0093] <Transition Temperature>

[0094] Transition temperature of optical glass (T) g Test according to the method specified in the national standard GB / T7962.16—2010.

[0095] In some embodiments, the transition temperature (T) of the optical glass of the present invention is... g The temperature range is 685℃ to 720℃, preferably 690℃ to 715℃, and more preferably 690℃ to 710℃. In some embodiments, the transition temperature (T) of the optical glass is... gThe values ​​can be 685℃, 687℃, 690℃, 693℃, 695℃, 697℃, 700℃, 703℃, 705℃, 707℃, 710℃, 713℃, 715℃, 717℃, 720℃, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0096] <shading>

[0097] The short-wavelength transmission spectral characteristics of the glass of this invention are expressed using colorimetry (λ). 70 λ5) represents λ. 70 λ5 refers to the wavelength corresponding to a glass transmittance of 70%, while λ6 refers to the wavelength corresponding to a glass transmittance of 5%. 70 The measurement was performed using a glass with a thickness of 10 ± 0.1 mm and two optically polished, parallel planes. The spectral transmittance was measured in the wavelength range from 280 nm to 700 nm, and wavelengths exhibiting 70% transmittance were recorded. Spectroscopic transmittance, or transmittance, is the value of transmittance when an intensity I is incident perpendicularly onto the aforementioned surface of the glass. in Light passes through the glass and exits from a plane with an intensity of I. out In the case of light, through I out / I in The quantity represented also includes the transmittance due to surface reflection loss on the aforementioned surfaces of the glass. Similarly, λ₅. In optical glass, λ 70 The smaller the value of λ5, the less coloration the glass itself has, and the higher the light transmittance.

[0098] In some embodiments, the tinting strength (λ) of the optical glass of the present invention 70 The chromaticity (λ) of the optical glass is 385 nm or less, preferably 380 nm or less, and more preferably 375 nm or less. In some embodiments, the chromaticity (λ) of the optical glass is... 70 The range can be 360nm, 361nm, 362nm, 363nm, 364nm, 365nm, 366nm, 367nm, 368nm, 369nm, 370nm, 371nm, 372nm, 373nm, 374nm, 375nm, 376nm, 377nm, 378nm, 379nm, 380nm, 381nm, 382nm, 383nm, 384nm, 385nm, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0099] In some embodiments, the tinting strength (λ5) of the optical glass of the present invention is 340 nm or less, preferably 335 nm or less, and more preferably 325 nm or less. In some embodiments, the tinting strength (λ5) of the optical glass can be 310 nm, 311 nm, 312 nm, 313 nm, 314 nm, 315 nm, 316 nm, 317 nm, 318 nm, 319 nm, 320 nm, 321 nm, 322 nm, 323 nm, 324 nm, 325 nm, 326 nm, 327 nm, 328 nm, 329 nm, 330 nm, 331 nm, 332 nm, 333 nm, 334 nm, 335 nm, 336 nm, 337 nm, 338 nm, 339 nm, 340 nm, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0100] <wear level>

[0101] Abrasion resistance (F) of optical glass A The wear amount (volume) refers to the ratio of the wear amount of the tested sample to the wear amount (volume) of the standard sample (H-K9 glass) under exactly the same conditions, multiplied by 100. The formula is as follows:

[0102] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100

[0103] Where: V—volume wear of the tested sample;

[0104] V0—Standard sample volume wear amount;

[0105] W—Mass wear of the tested sample;

[0106] W0—Standard sample mass wear amount;

[0107] ρ—Density of the sample being measured;

[0108] ρ0 — density of the standard sample.

[0109] In some embodiments, the abrasion degree (F) of the optical glass of the present invention A The lower limit for the wear resistance (F) is 75, preferably 80, and more preferably 85. In some embodiments, the wear resistance (F) of the optical glass of the present invention is... A The upper limit for (F) is 110, preferably 105, and more preferably 100. In some embodiments, the abrasion degree (F) of the optical glass is... AThe range can be 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0110] Young's Modulus

[0111] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.

[0112]

[0113] G=V S 2 ρ

[0114] In the formula: E is Young's modulus, Pa;

[0115] G is the shear modulus, Pa;

[0116] V T The transverse wave velocity is in m / s;

[0117] V S The longitudinal wave velocity is given in m / s.

[0118] ρ is the density of glass, in g / cm³ 3 .

[0119] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 105.0 GPa or higher, preferably 110.0 GPa or higher, and more preferably 118.0 GPa or higher. In some embodiments, the Young's modulus (E) of the optical glass can be 105.0 GPa, 105.5 GPa, 106.0 GPa, 106.5 GPa, 107.0 GPa, 107.5 GPa, 108.0 GPa, 108.5 GPa, 109.0 GPa, 109.5 GPa, 110.0 GPa, 110.5 GPa, 111.0 GPa, 111.5 GPa, 112.0 GPa, 112.5 GPa, 113.0 GPa, 113.5 GPa, 114.0 GPa, 11... 4.5 GPa, 115.0 GPa, 115.5 GPa, 116.0 GPa, 116.5 GPa, 117.0 GPa, 117.5 GPa, 118.0 GPa, 118.5 GPa, 119.0 GPa, 119.5 GPa, 120.0 GPa, 120.5 GPa, 121.0 GPa, 121.5 GPa, 122.0 GPa, 122.5 GPa, 123.0 GPa, 123.5 GPa, 124.0 GPa, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0120] <Effervescence>

[0121] The bubble degree of optical glass is tested according to the method specified in the national standard GB / T7962.8—2010.

[0122] In some embodiments, the bubble degree of the optical glass of the present invention is grade A or above, preferably grade A0 or above, and more preferably grade A. 00 class.

[0123] <Relative Partial Dispersion Deviation>

[0124] The following formula illustrates the relative partial dispersion (P) g,F ) and relative partial dispersion deviation (ΔP) g,F ) origin:

[0125] The relative partial dispersion of wavelengths x and y is expressed by the following equation (1):

[0126] P x,y =(n x -n y ) / (n F -n C (1)

[0127] According to the Abbe number formula, for most so-called "normal glass" (hereinafter, H-K6 and F4 are selected as "normal glass"), the following equation (2) holds:

[0128] P x,y =m x,y •v d +b x,y (2)

[0129] This linear relationship is based on P. x,y For the ordinate, v d The x-axis is used to represent the coordinates, where m is the x-axis. x,y Let b be the slope. x,y This is the intercept.

[0130] As is well known, the correction of a second-order spectrum, that is, the achromatic correction of more than two wavelengths, requires at least one type of glass that does not conform to the above formula (2) (i.e., its P). x,y The value deviates from Abbe's empirical formula, and the deviation is expressed as ΔP. x,y This means that each P x,y -v d The point is translated by ΔP relative to the "normal line" that conforms to equation (2) above. x,y Quantity, thus the ΔP of each glass x,y The numerical value can be obtained using the following formula (3):

[0131] P x,y =m x,y •v d +b x,y +ΔP x,y (3)

[0132] Therefore, ΔP x,y It quantitatively represents the deviation of the special dispersion characteristics compared to "normal glass".

[0133] Therefore, from the above, we can obtain the relative partial dispersion (P). g,F ) and relative partial dispersion deviation (ΔP) g,F The calculation formulas for ) are as follows: (4) and (5):

[0134] P g,F =(n g -n F ) / (n F -n C (4)

[0135] ΔP g,F =P g,F -0.6457 +0.001703v d (5)

[0136] In some embodiments, the relative partial dispersion deviation (ΔP) of the optical glass of the present invention g,F The relative partial dispersion deviation (ΔP) of the optical glass is -0.0030 or less, preferably -0.0050 or less, and more preferably -0.0070 or less. In some embodiments, the relative partial dispersion deviation (ΔP) of the optical glass is... g,F The range can be -0.0030, -0.0033, -0.0035, -0.0037, -0.0040, -0.0043, -0.0045, -0.0047, -0.0050, -0.0053, -0.0055, -0.0057, -0.0060, -0.0063, -0.0065, -0.0067, -0.0070, -0.0073, -0.0075, -0.0077, -0.0080, -0.0083, -0.0085, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0137] [Manufacturing methods for optical glass]

[0138] The manufacturing method of the optical glass of this invention is as follows: The glass of this invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials. After being batched according to conventional methods, the batched furnace charge is put into a melting furnace (such as a platinum or platinum alloy crucible) at 1100℃~1400℃ for melting. After clarification and homogenization, a homogeneous molten glass free of undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.

[0139] [Glass preforms and optical components]

[0140] Glass preforms can be manufactured from the produced optical glass using methods such as direct drop forming, grinding, or hot pressing. Specifically, glass preforms can be manufactured by directly and precisely drop-forming molten optical glass into precision glass preforms, or by machining such as grinding and polishing, or by hot pressing a preform made from optical glass for compression molding followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.

[0141] As described above, the optical glass of the present invention is useful for various optical components and optical designs. It is particularly preferred to form a preform from the optical glass of the present invention, and to use the preform for hot pressing, precision stamping, etc., to manufacture optical components such as lenses and prisms.

[0142] Both the glass preform and the optical element of the present invention are formed from the optical glass described above. The glass preform of the present invention possesses the excellent properties of optical glass; the optical element of the present invention possesses the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0143] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.

[0144] [equipment]

[0145] The optical glass of this invention, or the optical elements formed by the optical glass, can be used to manufacture devices such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment, monitoring equipment, AR (augmented reality) equipment, MR (mixed reality) equipment, VR (virtual reality) equipment, etc.

[0146] Example

[0147] <Example of Optical Glass>

[0148] To further illustrate and explain the technical solution of the present invention, the following non-limiting embodiments are provided.

[0149] In this embodiment, optical glass with the composition shown in Tables 2 and 3 was obtained by using the above-described optical glass manufacturing method, and the performance of each glass was measured by the test method described in this invention. The measurement results are shown in Tables 2 and 3.

[0150] Table 2.

[0151]

[0152]

[0153] Table 3.

[0154]

[0155]

[0156] <Example of Glass Prefabricated Components>

[0157] The glass obtained from optical glass examples 1# to 14# is used, for example, by grinding, or by molding such as hot pressing or precision stamping, to produce preforms of various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0158] <Optical Component Examples>

[0159] Annealing the preforms obtained from the above glass preform examples reduces the internal stress of the glass while fine-tuning the refractive index, so that the optical properties such as the refractive index reach the desired values.

[0160] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. Anti-reflective coatings can also be applied to the surface of the resulting optical elements.

[0161] <Equipment Example>

[0162] The optical elements obtained from the above-described optical element embodiments are optically designed and formed into optical components or assemblies by using one or more optical elements, and are thus assembled in various devices, such as imaging devices, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices that include such circuits and chips.

[0163] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0164] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. Optical glass, characterized in that, Its composition, expressed as a weight percentage, contains: B2O3: 8%–18%; SiO2: 3%–13%; La2O3: 31%–43%; ZnO: 1%–9%; Gd2O3: 7%–21%; Y2O3: 3%–14%; ZrO2: 2%–12%; Nb2O5: 2%–12%; Al2O3: greater than 0 but less than or equal to 5%, wherein the ratio of Al2O3 / (Y2O3+ZnO-SiO2) is 0.01–5.

00.

2. The optical glass according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: TiO2: 0–3%; and / or WO3: 0–3%; and / or Ta2O5: 0–3%; and / or Yb2O3: 0–5%; and / or Rn2O: 0–4%; and / or RO: 0–4%; and / or GeO2: 0–3%; and / or P2O5: 0–3%; and / or clarifying agent: 0–1%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that, Containing essential components B2O3, SiO2, La2O3, ZnO, Gd2O3, Y2O3, ZrO2, Nb2O5, and Al2O3, the composition is expressed as a weight percentage, with Al2O3 / (Y2O3+ZnO-SiO2) ranging from 0.01 to 5.

00. The refractive index n of the optical glass is... d The Abbe number ν ranges from 1.825 to 1.

875. d The value ranges from 40.50 to 46.00, and the Young's modulus is above 105.0 GPa.

4. The optical glass according to claim 3, characterized in that, Its composition, expressed as a weight percentage, contains: B2O3: 8%–18%; and / or SiO2: 3%–13%; and / or La2O3: 31%–43%; and / or ZnO: 1%–9%; and / or Gd2O3: 7%–21%; and / or Y2O3: 3%–14%; and / or ZrO2: 2%–12%; and / or Nb2O5: 2%–12%; and / or Al2O3: greater than 0 but less than or equal to 5%; and / or TiO2: 0–3%; and / or WO3: 0 ~3%; and / or Ta2O5: 0~3%; and / or Yb2O3: 0~5%; and / or Rn2O: 0~4%; and / or RO: 0~4%; and / or GeO2: 0~3%; and / or P2O5: 0~3%; and / or clarifying agent: 0~1%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

5. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage and satisfy one or more of the following conditions: 1) The ratio of Al2O3 / (Y2O3+ZnO-SiO2) is 0.05 to 3.00, preferably 0.10 to 1.00; 2) The ratio of (Gd2O3+Y2O3-B2O3) / Nb2O5 is 0.05 to 5.00, preferably 0.30 to 4.00, and more preferably 0.80 to 1.80; 3) The ratio of Gd2O3 / (ZnO+Y2O3) is 0.50 to 3.00, preferably 0.80 to 2.00, and more preferably 1.00 to 1.70; 4) The ratio of B2O3 to Y2O3 is 1.00 to 5.00, preferably 1.20 to 4.00, and more preferably 1.50 to 2.50; 5) The ZrO2 / ZnO ratio is 0.30 to 3.00, preferably 0.80 to 2.50, and more preferably 1.00 to 2.00; 6) The ratio of Al2O3 / (SiO2+ZnO+Y2O3-Gd2O3-Ta2O5) is 0.02 to 6.50, preferably 0.07 to 4.00, and more preferably 0.15 to 1.00; 7) The SiO2 / (ZnO-Ta2O5-TiO2-WO3-RO-Rn2O) ratio is 0.50 to 6.00, preferably 1.00 to 4.00, and more preferably 1.20 to 2.50; 8) The ratio of Al2O3 / (ZnO-Ta2O5-WO3) is 0.01 to 3.00, preferably 0.05 to 2.00, and more preferably 0.10 to 0.70; 9) The ratio of (ZnO+Nb2O5-SiO2) / (Gd2O3-Ta2O5-Y2O3) is 0.02 to 3.50, preferably 0.05 to 2.00, and more preferably 0.10 to 0.80; 10) The ratio of (Y2O3-ZnO-Ta2O5-WO3) / ZnO is 0.10 to 3.50, preferably 0.20 to 2.00, and more preferably 0.30 to 1.50; 11) The ratio of (ZnO+Rn2O) / Y2O3 is 0.10 to 1.00, preferably 0.20 to 0.90, and more preferably 0.40 to 0.80; 12) The ratio of (TiO2+Ta2O5+WO3) / Nb2O5 is 0.60 or less, preferably 0.30 or less, and more preferably 0.20 or less; 13) The ratio of (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.33 or less, preferably (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.20 or less, more preferably (TiO2+Ta2O5+WO3+Yb2O3+Rn2O+RO+GeO2) / ZnO is 0.15 or less, wherein Rn2O is one or more of Li2O, Na2O, and K2O, and RO is one or more of MgO, CaO, SrO, and BaO.

6. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: B2O3: 10%–17%, preferably B2O3: 12%–16%; and / or SiO2: 4%–11%, preferably SiO2: 5.5%–9%; and / or ZnO: 1.5%–8%, preferably ZnO: 2%–6%; and / or La2O3: 33%–42%, preferably La2O3: 36%–41%; and / or Gd2O3: 8%–20%, preferably Gd2O3: 10.5%–18%; and / or Y2O3: 5%–12%, preferably Y2O3: 6%–10%; and / or Yb2O3: 0%–3%, preferably Yb2O3: 0%–1%, more preferably Yb2O3-free; and / or ZrO2: 3%–10%, preferably ZrO2: 4%–8%; and / or Nb2O5: 3%–10%, preferably Nb2O5: 4%–8%; and / or Al2O3: 0.1%–4%, preferably Al2O3: 0.5%–2.5%; and / or TiO2: 0%–10%; ~2%, preferably TiO2: 0~1%; and / or WO3: 0~2%, preferably WO3: 0~0.5%, more preferably WO3-free; and / or Ta2O5: 0~2%, preferably Ta2O5: 0~0.5%, more preferably Ta2O5-free; and / or Rn2O: 0~2%, preferably Rn2O: 0~1%, more preferably Rn2O-free; and / or RO: 0~2%, preferably RO: 0~1%, more preferably RO-free; and / or GeO2: 0~2% The preferred concentrations are: GeO2: 0-1%, more preferably without GeO2; and / or P2O5: 0-2%, preferably P2O5: 0-1%, more preferably without P2O5; and / or clarifying agent: 0-0.5%, preferably clarifying agent: 0-0.2%, wherein Rn2O is one or more of Li2O, Na2O, and K2O, RO is one or more of MgO, CaO, SrO, and BaO, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

7. The optical glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the optical glass d The Abbe number is 1.825–1.875, preferably 1.830–1.870, more preferably 1.840–1.858; and / or the Abbe number ν. d The coefficient of thermal expansion is 40.50 to 46.00, preferably 41.00 to 45.00, more preferably 41.50 to 44.00; and / or the Young's modulus is 105.0 GPa or more, preferably 110.0 GPa or more, more preferably 118.0 GPa or more; and / or the coefficient of thermal expansion α is 40.50 to 46.00, preferably 41.00 to 45.00, more preferably 41.50 to 44.00; and / or the coefficient of thermal expansion α is 105.0 GPa or more, preferably 110.0 GPa or more; and / or the coefficient of thermal expansion α is 118.0 GPa or more. 100℃ / 300℃ 100×10 -7 / K or less, preferably 95×10 -7 / K or less, preferably 90×10 -7 / K or below; and / or water resistance stability of Class 2 or above, preferably Class 1; and / or weather resistance of Class 2 or above, preferably Class 1; and / or density of 5.30 g / cm³. 3 The preferred value is 5.20 g / cm³. 3 The following is a preferred value: 5.10 g / cm³ 3 The following is a further preferred value: 5.05 g / cm³ 3 The following; and / or Knoop hardness is 610×10 7 Pa or higher, preferably 630 × 10 Pa 7 Pa or higher, more preferably 650 × 10 Pa 7 Pa or above; and / or a transition temperature of 685°C to 720°C, preferably 690°C to 715°C, more preferably 690°C to 710°C; and / or a colorimetric intensity λ 70 The wavelength is 385nm or less, preferably 380nm or less, more preferably 375nm or less; and / or the colorimetric intensity λ5 is 340nm or less, preferably 335nm or less, more preferably 325nm or less; and / or the abrasion degree is 75-110, preferably 80-105, more preferably 85-100; and / or the bubble degree is A grade or higher, preferably A0 grade or higher, more preferably A 00 Level; and / or relative partial dispersion deviation ΔP g,F It is less than -0.0030, preferably less than -0.0050, and more preferably less than -0.0070.

8. A glass precast component, characterized in that, It is made of the optical glass described in any one of claims 1 to 7.

9. An optical element, characterized in that, It is made of the optical glass described in any one of claims 1 to 7, or of the glass preform described in claim 8.

10. A device, characterized in that, It contains the optical glass according to any one of claims 1 to 7, and / or contains the optical element according to claim 9.